The Approach Behavior to Angry Words in Athletes—A Pilot Study - Xia, Xue; Zhang, Jian; Wang, Xiaoshuang; Wang, Xiaochun (Frontiers in Behavioral Neuroscience, 2019)
An increasing number of studies have found that athletes have a higher level of aggression than non-athletes. Anger is an important factor in the generation of aggressive behavior, and anger has been found to relate to both approach behavior and avoidance behavior. The present pilot study compared the aggression level of athletes and non-athletes using the Buss-Perry Aggression Questionnaire and examined the responses of participants to anger-related stimuli using the manikin task, a paradigm that measures approach-avoidance behavior. In total, 15 athletes and 15 non-athletes finished the questionnaire and the manikin task, which included two conditions. In the anger approach condition, participants were asked to approach anger-associated words and to avoid neutral words. The instructions for the anger avoidance condition were the opposite (i.e., move away from the anger-associated words and toward the neutral words). Brain activity was recorded during the manikin task. Results showed that compared with non-athletes, athletes had significantly higher physical aggression on the questionnaire. The athlete group showed significantly shorter reaction time in anger approach condition than anger avoidance condition. Theta oscillation activity induced during the anger approach condition was significantly lower than that during the anger avoidance condition in the athlete group. No significant correlation was found in present pilot study. These findings may suggest that when anger-related stimuli are present, athletes are more likely to approach, indicating stronger behavioral approach motivation that may result in aggressive behavior.